Inflammatory Cytokines and SIRT1 Levels in Subcutaneous Abdominal Fat: Relationship With Cardiac Performance in Overweight Pre-diabetics Patients - Sardu, Celestino; Pieretti, Gorizio; D'Onofrio, Nunzia; Ciccarelli, Feliciano; Paolisso, Pasquale; Passavanti, Maria B.; Marfella, Raffaele; Cioffi, Michele; Mone, Pasquale; Dalise, Anna M.; Ferraraccio, Franca; Panarese, Iacopo; et al. (Frontiers in Physiology, 2018)
Objectives: In obese patients the superficial adipose tissue expresses cytokines, and sirtuins, that may affect myocardial function. In this study, we investigated the effect of metformin therapy added to a hypocaloric diet on the inflammatory pattern and cardiac performance (MPI) in obese patients with pre-diabetic condition. Materials and Methods: Fifty-eight obese patients that were enrolled for abdominoplastic surgery were divided into patients with pre-diabetic condition (n 40) and normo-glycemic patients (n18). Patients with pre-diabetic condition were randomly assigned to metformin therapy added to a hypocaloric diet (group 1, n 20) or to a hypocaloric diet therapy alone (group 2, n20). Patients with normo-glycemic condition were assigned to a hypocaloric diet therapy. Results: During enrollment, obese patients with a pre-diabetic condition (group 1 and 2) presented higher glucose values, lower values of insulin, and higher values of the homeostasis model for the assessment of insulin resistance (HOMA-IR) than obese patients with normo-glycemic condition(group 3). In addition, they had higher values of C Reactive protein (CRP), interleukin 6 (IL6), and lower values of sirtuin 1(SIRT1). In the 12th month of the follow-up, metformin therapy induced in patients with pre-diabetic condition (group 1) a significant reduction of glucose values, HOMA-IR, and inflammatory markers such as CRP (1.04 ± 0.48 vs. 0.49 ± 0.02 mmol/L, p < 0.05), IL6 (4.22 ± 0.45 vs. 3.33 ± 0.34 pg/ml, p < 0.05), TNFα (6.95 ± 0.59 vs. 5.15 ± 0.44 pg/ml, p < 0.05), and Nitrotyrosine (5,214 ± 0,702 vs. 2,151 ± 0,351 nmol/l, p < 0.05). This was associated with a significant reduction of Intima-media thickness (1.01 ± 0.15 vs. 0.86 ± 0.15 mm, p < 0.05), Septum (14 ± 2.5 vs. 10.5 ± 2 mm, p < 0.05), Posterior wall (11 ± 1.5 vs. 8 ± 1 mm, p < 0.05), LV mass (192.5 ± 49.5 vs. 133.2 ± 37.6 g, p < 0.05) and of MPI (0.58 ± 0.03 vs. 0.38 ± 0.02, p < 0.05). At 12 months of follow-up, group 2 experienced only a reduction of cholesterol (4.15 ± 0.94 vs. 4.51 ± 0.88 mmol/L, p < 0.05) and triglycerides (1.71 ± 1.18 vs. 1.83 ± 0.54 mmol/L, p < 0.05). At 12 months of follow-up, group 3 experienced a significant reduction of inflammatory markers, and also of echographic parameters, associated with amelioration of myocardial performance. To date, IL6 expression was related to higher values of left ventricle mass (R-value 0.272, p-value 0.039), and to higher IMT (R-value 0.272, p-value 0.039), such as those observed for CRP (R-value 0.308, p-value 0.021), for glucose blood values (R-value 0.449, p-value 0.001), and for HOMA-IR (R-value 0.366, p-value 0.005). An inverse correlation was found between subcutaneous fat expression of SIRT1 and myocardial performance index (R-value−0.236, p-value 0.002). Conclusion: In obese patients with pre-diabetic condition a metformin therapy may reduce inflammation and oxidative stress, and this may be associated with the amelioration of the cardiac performance. Clinical research trial number: NCT03439592.